Understanding Mediterranean Pasture Dynamics: General Tree Cover vs. Specific Effects of Individual Trees - De Miguel, José Manuel; Acosta-Gallo, Belén; Gómez-Sal, Antonio (Rangeland Ecology & Management, 2013)
The study investigated the effect of general and homogeneous tree cover on grassland composition on an extensive Mediterranean rangeland with sparse oak trees in central Spain. We analyzed this effect together with other significant factors identified in this type of rangeland: topography and plowing. Data were collected in the 1984 growing season and they form part of a historical database on the characteristics of vegetation and livestock behavior; these data refer to grasslands below and away from the tree crowns of 91 individual trees, located in different topographical positions and in areas that were last plowed at different times.We used multivariate analyses to identify the main compositional trends of variation in pasture communities. The results indicate that the herbaceous community below tree crowns was more similar to that of the lowland areas than to the nearby areas away from the tree. This result supports the idea of tree cover in semiarid rangelands as a factor attenuating the effects on pastures of environmental conditions typical of high and intermediate topographical positions—generally presenting low soil moisture and fertility. Coupled with this, we also found effects of some individual trees related with the way livestock uses them as shelter and resting places. Our results indicate that the role played by dispersed trees in the management of this type of rangeland should be analyzed at two complementary spatial scales: the overall effect of tree cover as a factor acting at landscape scale and the specific effect of some individual trees acting at a more detailed scale.
Keywords: free-ranging livestock; pasture management; Quercus ilex; scattered trees; Silvopastoral systems; topography effect